Instrument validation for Functional Health Literacy competence and associated factors (Research, Society and Development, 2020)
Objective: To validate an instrument to assess functional health literacy skills for family members of children and verify its association with sociodemographic characteristics. Method: Cross-sectional study with 302 parents of children under one year old, who participated on clinical validation of the test in the Brazilian version, in primary care units in a city of West Paraná, in 2019 and 2020. A descriptive and inferential statistics analysis was carried out. Results: The internal confidence of the test, measured by the Kuder-Richardson method, was substantial (KR-20 = 0.70) and maintained in the confirmatory factor analysis a dimension of the scale, as in the original. The functional health literacy was defined by the median of responses, obtaining 70 cutoff points. Among the participants, 67.4% obtained satisfactory functional health literacy. The profile of parents demonstrated predominance of mothers (93.4%), the average age of the participants were 28.3 years, 53.6% completed high school, the predominant income was up to two minimum wages and 55.3% used exclusively the primary care unit for children health assistance. In the correlation between sociodemographic characteristics and functional health literacy, higher income and more years of schooling influenced the best literacy performance results. Conclusion: The study contributes with a trustworthy instrument to verify functional health literacy for children care, unprecedented in Brazil.